RESPON KONSUMEN TERHADAP IKLAN EMAIL DARI BIRO TUR DAN PERJALANAN DI INDONESIA - Jonathan Kurniawan Halim; Christina R. Honantha; Silvia Margaretha (Perpustakaan Universitas Surabaya, 2018)
This study aims to determine and analyze consumer response to email advertising from online agent Tour and Travel in Indonesia.This type of research is causal research with quantitative approach. This study using purposive sampling approach with an assessment of the researchers who can be made respondents in accordance with the characteristics of the population. Thecharacteristics of the population is consumer who buy and used online agent Tour and Travel 2 times in the last 1 year, live in Indonesia, minimum of level education is bachelor.Respondents in t his study amounted to 125 people. The analysis in this study using a model of SEM (Structural Equation Modeling) through SPSS software version 22.0 for Windows and AMOS version 21.0 for Windows for testing Measurement and Structural Model.The result of this study indicate that with the intention of consumers to buy, build relationship, and trust with good service then consumers will read, open, take advantage of email advertising from Tours and Travel in Indonesia and even consumers want to get email ads in the future.